물류 및 공급망관리 연구의 50년: 과거, 현재, 그리고 미래 - 문일경; 김병수; 정병도; 신영철 (대한산업공학회지, 2024)
As technological advancements have rapidly progressed over time periods, research in logistics and supply chain management has also evolved accordingly. This paper aims to analyze the direction of research development in these research areas by extracting keywords from three major journals. Based on the keywords, a semantic network analysis was conducted to visualize and analyze the relationships between the keywords. Furthermore, the recent research trends were examined by dividing the keywords associated with each research area into different time periods. For logistics management, keyword analyses were conducted based on six categories over time periods. In supply chain management, keyword analyses were conducted based on two categories, which were further divided into two and three sub-categories respectively, for a more detailed analysis. Additionally, we review the annual reports of funded research projects between 2018 and 2024, specifically within the scope of supply chain risk management, supported by the division of ICT․Convergence Research. By comparing these trends with key concepts required in Industry 5.0, we suggest future research directions in the areas of logistics and supply chain management. Accordingly, we expect to contribute to understanding the past and present of logistics and supply chain management, while offering insights into its future directions. In addition to its academic contributions, we expect to provide practical insights that can help industries enhance their competitiveness in a rapidly changing environment.
Keywords: Logistics Management; Supply Chain Management; Industry 5.0; Logistics 5.0